2022
DOI: 10.1002/ccd.30100
|View full text |Cite
|
Sign up to set email alerts
|

Protective ballooning technique for prevention of side branch occlusion in coronary nonleft main true bifurcation lesions: A single‐center study

Abstract: Objectives We aimed to evaluate the efficacy of a protective ballooning technique in preventing side branch (SB) occlusion and to assess the long‐term clinical outcomes for coronary nonleft main true bifurcation lesions. Background SB occlusion is a major complication associated with percutaneous coronary intervention (PCI) for coronary bifurcation lesions. Methods Patients were consecutively enrolled and randomly assigned to protective ballooning technique or jailed wire technique group. Periprocedural and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Two were added by reviewing the relevant references. Finally, 13 studies involving 1789 patients were enrolled, including four published in English and nine published in Chinese [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. The flowchart for identifying these studies is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two were added by reviewing the relevant references. Finally, 13 studies involving 1789 patients were enrolled, including four published in English and nine published in Chinese [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. The flowchart for identifying these studies is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The baseline information of the enrolled studies and participants is displayed in Tables 1A , 1B , 2 (Ref. [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]). There are nine RCTs and four observational studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the main branch and branch pre-expansion, a Bingo drug-eluting balloon of 2.5 mm×15.0 mm was administered at the D1 opening lesion. Under the protective ballooning technique, [8] a Resolute Integrity 2.5 mm×18.0 mm stent was implanted in the LAD lesion with acceptable residual stenosis of the D1 opening. A Resolute Integrity 2.25 mm×30.00 mm stent was implanted in the RAM lesion (Figure 1).…”
Section: Casementioning
confidence: 99%